2018
DOI: 10.1103/physrevlett.120.080501
|View full text |Cite|
|
Sign up to set email alerts
|

Multiparameter Estimation in Networked Quantum Sensors

Abstract: We introduce a general model for a network of quantum sensors, and we use this model to consider the following question: When can entanglement between the sensors, and/or global measurements, enhance the precision with which the network can measure a set of unknown parameters? We rigorously answer this question by presenting precise theorems proving that for a broad class of problems there is, at most, a very limited intrinsic advantage to using entangled states or global measurements. Moreover, for many estim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
252
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(255 citation statements)
references
References 63 publications
1
252
1
1
Order By: Relevance
“…Достижения в этой области позволят существенно повысить точность и разрешение измерений, а также сделать многие измерения неинвазивными. В этом направлении уже сегодня есть много практических достижений [Proctor, 2017].…”
Section: рис 2 схема квантового протокола передачи информации Bb84unclassified
“…Достижения в этой области позволят существенно повысить точность и разрешение измерений, а также сделать многие измерения неинвазивными. В этом направлении уже сегодня есть много практических достижений [Proctor, 2017].…”
Section: рис 2 схема квантового протокола передачи информации Bb84unclassified
“…It has already found use in proving the fundamental limits of covert sensing [11]. Other potential applications of our result include finite-length analysis of channel estimation in quantum key distribution protocols [18], distributed sensing using shared entanglement [19][20][21][22][23], and other problems requiring bounding the fundamental limits of sensing an unknown parameter embedded in a correlated field. We denote operators with a circumflex (e.g.,ρ for density operators) and estimators with a tilde (e.g.,μ orθ ).…”
Section: Introductionmentioning
confidence: 99%
“…(19), is an upper bound on the QFI that accounts for thermal photons in the environment and an arbitrary input state. Our bound is a function of the number of modes n, the mean and variance of the total number of photons N S in the n-mode probe, and the channel transmissivity η and mean thermal photon number per moden B .…”
Section: Introductionmentioning
confidence: 99%
“…For example, when the bipartite entanglement of two-mode squeezed states is leveraged in target detection, it provides a signal-to-noise ratio advantage over that of the optimum classical scheme [4][5][6][7][8]. Prior work has shown that multipartite entanglement between distributed sensors could yield significant sensitivity enhancement in estimating the weighted sum of unknown parameters in the sensor network [9,10]. However, these distributed quantum-sensing protocols rely on photonic discrete-variable multipartite entanglement, which, to date, can only be probabilistically generated and is extremely vulnerable to environmental loss.…”
Section: Introductionmentioning
confidence: 99%
“…Before proceeding, it is worth contrasting the approach we take with recent work on distributed quantum sensing [9,10]. Reference [9]'s distributed phase sensing required twin Fock-state generation and photon-number resolving detectors to realize Heisenberg scaling, and Ref.…”
Section: Introductionmentioning
confidence: 99%